1995
DOI: 10.1097/00000542-199510000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-Protamine Complexes Cause Pulmonary Hypertension in Goats

Abstract: H-P complexes play a major role in pulmonary hypertension after protamine reversal of heparin, and thromboxane A2 is a main mediator of the pulmonary hypertensive response to H-P complexes in goats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 11 publications
1
9
0
2
Order By: Relevance
“…Morel et al (3) and Horiguchi et al (20) demonstrated that the heparinprotamine complex induced bronchoconstriction and pulmonary hypertension in vivo, respectively. These constrictive phenomena are thought to be induced by thromboxane A 2 generation after protamine reversal of heparin (3,20). Thus, the direct inhibitory effect of heparin-protamine complex on the carbachol-induced contraction of airway smooth muscle seen in this study is not incompatible with these data.…”
Section: Discussionsupporting
confidence: 58%
“…Morel et al (3) and Horiguchi et al (20) demonstrated that the heparinprotamine complex induced bronchoconstriction and pulmonary hypertension in vivo, respectively. These constrictive phenomena are thought to be induced by thromboxane A 2 generation after protamine reversal of heparin (3,20). Thus, the direct inhibitory effect of heparin-protamine complex on the carbachol-induced contraction of airway smooth muscle seen in this study is not incompatible with these data.…”
Section: Discussionsupporting
confidence: 58%
“…Beyond the speculative aspects on human disease, our data and previous investigations (60) support the fact that different Nox in different species and models of PH can contribute to PH development. The mechanism described in the current article would be taken into account for PH development not only in humans, but also in animals such as cattle, horses, sheep, goats, and dogs (26,34,37).…”
mentioning
confidence: 99%
“…The changes seen were limited solely to RL, and not in either EL or the chest wall mechanical properties. This is not unexpected, given that protamine complexes can enhance the production of thromboxanes via the archidonic acid pathway, with resultant bronchoconstriction and pulmonary hypertension (14). Bronchoconstriction should I4I affect predominantly RL through narrowing of the mid-size (&dquo;resistance&dquo;) airways, and not necessarily EL, which is related to more distal, complex alveolar processes.…”
Section: Discussionmentioning
confidence: 98%